2023
DOI: 10.3390/cancers15123202
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Colorectal Cancer: Current Insights

Fauzia Ullah,
Ashwathy Balachandran Pillai,
Najiullah Omar
et al.

Abstract: Over the past decade, the incidence of colorectal cancer has increased in individuals under the age of 50 years. Meanwhile, the incidence has gradually decreased in the older population. As described herein, we reviewed the available literature to summarize the current landscape of early-onset colorectal cancer, including risk factors, clinicopathological presentation, genetic makeup of patients, and management. Currently, early-onset colorectal cancer is treated similarly as late-onset colorectal cancer, yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 124 publications
0
3
0
Order By: Relevance
“…In this systematic review, EOCRC was defined as colorectal cancer diagnosed in individuals under the age of 50. This definition aligns with emerging research trends and clinical observations indicating a distinct epidemiological pattern and clinical presentation in younger patients compared to their older counterparts [4]. The choice of this age cutoff was based on the intention to explore and identify the specific challenges and outcomes faced by this particular demographic group.…”
Section: Definitionsmentioning
confidence: 92%
See 1 more Smart Citation
“…In this systematic review, EOCRC was defined as colorectal cancer diagnosed in individuals under the age of 50. This definition aligns with emerging research trends and clinical observations indicating a distinct epidemiological pattern and clinical presentation in younger patients compared to their older counterparts [4]. The choice of this age cutoff was based on the intention to explore and identify the specific challenges and outcomes faced by this particular demographic group.…”
Section: Definitionsmentioning
confidence: 92%
“…The incidence of colorectal cancer (CRC) among younger adults has been on the rise globally, presenting unique challenges in management and survivorship [1,2]. Traditionally considered a disease of older adults, the increasing trend of early-onset colorectal cancer (EOCRC), defined as CRC diagnosed in individuals under the age of 50, has garnered significant attention in the medical community [3,4]. Epidemiological studies have indicated a steady increase in EOCRC prevalence across diverse populations, suggesting the need for focused research on its implications.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, half of the cases diagnosed with early-onset CRC are sporadic, without associated hereditary syndromes or familial CRC [12]. There is increasing evidence to suggest that early-onset CRC is distinct from late-onset CRC, not only in terms of age of presentation but also in terms of clinical manifestation, location, and histopathological characteristics [13,14]. This has prompted researchers to consider early-onset CRC as a unique entity, with a gap in the literature as to the histopathological subtype that may be contributing to its rising incidence [15,16].…”
Section: Introductionmentioning
confidence: 99%